2012
DOI: 10.1089/jop.2011.0160
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Antiadipogenic Profile of Latanoprost, Travoprost, Bimatoprost, and Tafluprost in Human Orbital Preadiopocytes

Abstract: Latanoprost, travoprost, bimatoprost, and tafluprost inhibited human preadipocyte differentiation and intracellular lipid accumulation. Morphologic and metabolic changes in orbital adipocytes caused by PGF2α analogs are a possible pathophysiologic explanation of superior eyelid deepening in patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
2
40
0
1
Order By: Relevance
“…PGF 2a also inhibited adipogenesis in OFs, as reported by Choi and colleagues (30), although these authors did not investigate cells from GO orbits, whereas our study illustrates that they remain highly responsive to the drug and have not become resistant, for example, by losing PGF 2a receptors.…”
Section: Discussionsupporting
confidence: 78%
“…PGF 2a also inhibited adipogenesis in OFs, as reported by Choi and colleagues (30), although these authors did not investigate cells from GO orbits, whereas our study illustrates that they remain highly responsive to the drug and have not become resistant, for example, by losing PGF 2a receptors.…”
Section: Discussionsupporting
confidence: 78%
“…Filippopoulos et al described upper deep eyelid creases, apparent enophthalmos and attenuation of dermatochalasis (15) . Based mainly on the pharmacological properties of bimatoprost, the hypothesis of these eyelid and orbital changes were resulting from the reduction of preaponeurotic and orbital fat was created (13,16,17) . Although there is a slight difference in the orbital anatomy and physiology among species, the knowledge gained in animal studies can assist in research in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that bimatoprost reduces the amount and volume of adipose cells. Choi et al concluded that bimatoprost inhibits both the differentiation of pre-adipocytes and intracellular lipid accumulation (16) . According to Kim, prostaglandin analogues present an inhibitory event especially in the late stage of adipocyte differentiation (17) .…”
Section: Discussionmentioning
confidence: 99%
“…These case reports are the first that suggest that this mechanism could also be active in vivo. Choi et al (2012) compared bimatoprost with PGF 2a and three analogs on isolated primary human orbital preadipocytes for antiadipogenic potential. All drug treatments reduced adipocyte differentiation, with bimatoprost producing the most significant reduction (Choi et al, 2012).…”
Section: Adipose Tissuementioning
confidence: 99%
“…Choi et al (2012) compared bimatoprost with PGF 2a and three analogs on isolated primary human orbital preadipocytes for antiadipogenic potential. All drug treatments reduced adipocyte differentiation, with bimatoprost producing the most significant reduction (Choi et al, 2012). Although this study highlights that adipocytes from the target tissue are affected similar to other adipocytes in vitro, a lack of dose-ranging studies leaves the relative effectiveness of any one drug in question.…”
Section: Adipose Tissuementioning
confidence: 99%